Persistently curly hair phenotype with the use of nivolumab for squamous cell lung cancer. (December 2017) - Dasanu, Constantin A; Lippman, Scott M; Plaxe, Steven C
Increasing use of programmed cell death protein 1/programmed cell death protein 1 ligand inhibition for the treatment of patients with various malignancies such as advanced lung cancer, kidney cancer, and melanoma has resulted in valuable clinical responses, along with the occurrence of new and often puzzling side effects. Known cutaneous effects of CTLA4 and programmed cell death protein 1/programmed cell death protein 1 ligand inhibitors include generalized pruritus, vitiligo, maculopapular lesions, and lichenoid skin eruptions. Alopecia has been the only hair effect previously associated with this class of agents. We describe herein the first case of a persistent curly hair phenotype with the use of nivolumab in a patient with metastatic squamous cell lung cancer.